(3Led GdZQGFHs - (3GdfjSGHhQj , eMehO Hf CHj GdMSjf GdfjSGHhQj, CHh GdbGSe (B- (3fLe GdOjf (B- (3HjGf GdMb,J (B550 (3g` s ((3WGgQ Hf CHj RjO GdNWjHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi HMeOg GHJOGA cd ebGd CeG HYO , aEf dcd Yde QLGdkG HCjOjge JQJaY CYdGeg s
(3BNQgG (B:s
(3bGd GdfeQ Hf JhdH (B: (3aEPG eG de jUH QTOkG cGf HYV Gddhe KfjGfG Ci jdheI GdfGS dhekG HYO Gdjhe YeQ QVi Gddg Yfg (B: (3GddHf dG jehJ Ci jfRY GdTHg HGdQVjY Edi GdXFQ ef CLd GddHf hGddg CYde s
(3HChdgG Jedc SfI (B732s
(3LeY ajg ZQjH GdMOjK hQJHI Ydi CQHYI hYTQjf cJGHkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B167 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B157s
Keywords: (3GddZIs